Hybrid Carrier Tracking with Decoupled Local Filters in Multi-Frequency GNSS Receivers - Rong Yang; Jihong Huang; Xingqun Zhan (Navigation)
The collaborative efforts of multi-frequency receivers have proven to be a significant advantage in the challenging environments of global navigation satellite system carrier tracking. This paper delves into the exploration of multi-carrier hybrid tracking, employing both phase-locked loop and frequency-locked loop observations to maximize tracking capability. This hybrid approach conducts distributed phase tracking and centralized Doppler frequency tracking within decoupled local filters to accommodate the frequency dispersion and reduce dimensionality. Subsequently, global assimilation is performed to adjust filter weights for performance optimization. Theoretical analysis affirms that this hybrid design can achieve tracking performance close to optimality when compared with classic centralized estimation, significantly outperforming fully distributed approaches. Additionally, simulations of ionospheric scintillation validate the effectiveness of the proposed hybrid carrier tracking design.